2012
DOI: 10.26719/2012.18.12.1239
|View full text |Cite
|
Sign up to set email alerts
|

Access and barriers to health care delivery in Arab countries: a review

Abstract: This paper reviews some of the main obstacles encountered by the population (or rather by different social groups) in accessing health services in Arab countries. These obstacles can be social and cultural, administrative and organizational or financial and may impact on gender and ethnic groups to different degrees. Governments are urged to address the health inequalities that result from these obstacles and promote equity, solidarity and fairness through social policies that enhance social and national devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 23 publications
4
58
0
Order By: Relevance
“…A need exists for better and improved establishment of public health systems in the Gulf Cooperation Council (GCC) countries [15]. The policies should be within the national health priorities, focusing on the current and emerging health challenges e.g.…”
Section: Public Health Systems In Gulf Cooperation Council (Gcc) Counmentioning
confidence: 99%
“…A need exists for better and improved establishment of public health systems in the Gulf Cooperation Council (GCC) countries [15]. The policies should be within the national health priorities, focusing on the current and emerging health challenges e.g.…”
Section: Public Health Systems In Gulf Cooperation Council (Gcc) Counmentioning
confidence: 99%
“…This paper is the last in a series of five reviews about the health services provided to groups with special needs in the Arab world [1][2][3][4]. The challenges faced by older people as well as people with functional and mental disabilities are highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that physicians practising in the region may not have received much training in some of these topics (12). Additionally, they may consider some of these conditions to be outside of their sphere of responsibility (13). Therefore, CME on these important topics would be expected to improve the scope and quality of health care provided in these UNRWA primary care clinics.…”
Section: Discussionmentioning
confidence: 99%